SHARE
TWEET

adsads

a guest Feb 19th, 2020 79 Never
Not a member of Pastebin yet? Sign Up, it unlocks many cool features!
  1. 27 ^ 1 - x = 9 ^ 2x + 3
  2. 27 = 3 ^ 3
  3. 9 = 3 ^ 2
  4. 3 ^ 3(1 - x) = 3 ^ 2(2x + 3)
  5. Get rid of the base 3 on both sides and just leave the exponents.
  6. 3(1 - x) = 2(2x + 3)
  7. 3 - 3x = 4x + 6
  8. -3 = 7x
  9. x = -3/7
RAW Paste Data
We use cookies for various purposes including analytics. By continuing to use Pastebin, you agree to our use of cookies as described in the Cookies Policy. OK, I Understand
Top